The Thermoelectric Properties of Vacuum Evaporated In0.8Se0.2 alloy Thin Film Nanostructure - Jareeze, Amar H (Al-Nahrain Journal of Science, 2013)
الخلاصة:In0.8Se0.2 thin films were prepared on glass substrate by vacuum evaporation technique at a pressure of 10-5 torr. The crystallinity of the thin film has been analyzed by X-ray diffraction, which show the formation of hexagonal system, Scanning Electron and Atomic Force microscopy examination indicates that the grain size have nearly spherical shape with diameters range from 100nm to 600nm. The thermoelectric properties of the films were determined over the thickness of 200nm Thermoelectric properties show a negative sign exhibiting n- type semiconducting nature of films. The electrical conductivity and Seebeck coefficient were measured from room temperature up to about 423 K, the Seebeck coefficient increases with increasing temperature and the electrical conductivity decreases with increasing the temperature of the sample the power factor coefficient increases with increasing temperature.